Penerapan Model Pembelajaran Problem Based Learning (PBL) dengan Menggunakan Aplikasi Edmodo untuk Meningkatkan Pemahaman Konsep dan Keterampilan Komunikasi Mahasiswa - Nosi Qadariah (Journal on Education, 2023)
The development of education demands a learning mechanism that is adaptive to all conditions. The results of observations show that students' understanding of concepts and communication skills is still low. The factor for the low understanding of concepts and student communication skills is that there is a lack of variety in the implementation of lectures. The solution to this is learning by using the problem-based learning (PBL) model using the edmodo application. The purpose of the study was to analyze the effect of applying the Problem Based Learning (PBL) learning model using the edmodo application in improving students' understanding of concepts and communication skills. This type of research is a quasi experiment. The research design is nonrandomized pretest-pottest groups. PBL learning model using edmodo application can improve students' concept understanding (p-value = 0.008 < α (α = 0.05) and can improve students' communication skills (p-value = 0.008 < α (α = 0.05).